PENGARUH KETERBUKAAN PERDAGANGAN, KORUPSI, DAN STABILITAS POLITIK TERHADAP PERTUMBUHAN EKONOMI DI NEGARA ASEAN-6 - Imtinan Ira Setiawaty; Ida Ayu Meisthya Pratiwi (Jurnal Ekonomi dan Bisnis, 2026)
Growth in the ASEAN region shows that six of the eleven member countries are still in the middle-income category with an average GDP per capita of around USD 4.656 and stagnant economic growth for more than a decade, amid relatively high trade openness and poor institutional quality. This study analyzes the impact of trade openness, corruption, and political stability on economic growth in ASEAN-6 countries (Indonesia, Malaysia, Thailand, Cambodia, Philippines, and Vietnam). This study uses secondary panel data from the six countries for the period 2013–2023, with economic growth (GDP per capita) as the dependent variable and the trade openness ratio, corruption perception index, and political stability index as the independent variables. The analysis was conducted using panel data regression with the Fixed Effect Model (FEM) approach. The result show that simultaneously, the three variables have a significant effect on the economic growth of ASEAN-6. Partially, trade openness and the corruption perception index have a positive significant effect, which means that increased international trade activity and a decrease in corruption level can drive economic growth. Meanwhile, political stability has a positive but insignificant effect. Thus, the six countries need to maintain and expand trade openness, strengthen efforts to eradicate corruption by increasing the transparency and accountability of public institutions, and maintain policy consistency in order to create an environment conducive to investment and sustainable economic development.